Tongue root harmony and vowel contrast in northeast Asian languages - Ko, Seongyeon (Turcologica, 2018)
This book investigates the synchrony and diachrony of the vocalism of a variety of Northeast Asian languages, especially Korean, Mongolic, and Tungusic languages, traditionally known as?Altaic? and more recently as?Transeurasian.? 0After careful examinations of the phonetics and phonology of vowels in each variety, the author presents a formal synchronic analysis of more than 35 languages and dialects, past and present, within the framework of Contrastive Hierarchy (CH).